Composição lipidica e atividade antioxidante do leite e do sangue de búfalas suplementadas com óleo de linhaça e vitamina e na dieta - Agustinho, Bruna Calvo (2017)
The objective of this study was to evaluate the effect of the addition of flaxseed oil and/or vitamin E on DM (dry matter) intake, nutrient digestibility, antioxidants and oxidative stability in blood and milk and milk lipid profile of lactating buffaloes. Four crossbred buffalo females were used, after the peak of lactation (97±22 days of lactation), mean body weight of 655±37 kg submitted to a daily milking with the presence of the calf, distributed in a 4x4 Latin square design, in a 2x2 factorial arrangement (Oil: presence and absence, and vitamin E: presence and absence). This is how the experimental diets were composed: control (absence of oil and vitamin); Diet with flaxseed oil, 25 g/kg DM; Diet with vitamin E, 375 IU/kg DM; Diet with flaxseed oil (25 g/kg DM) and vitamin E (375 IU/kg DM). The oil was weighed together with the concentrate, while vitamin E was supplied in a portion of approximately 50 g of the total mixed feed, after the total intake of that portion the rest of the feed was provided. The intake of ethereal extract increased and non-fibrous carbohydrates reduced in the diets with flaxseed oil. Blood parameters had no effect (P>0.05) on the addition of flaxssed oil and/or vitamin E. However, the addition of oil reduced the digestibility of neutral detergent fiber (P<0.01), increased digestibility of ethereal extract (P<0.01) and increased (P<0.05) milk production and density, as well as TBARS and conjugated diene. In addition, there was a tendency for long chain fatty acids (FA) to increase (P=0.06), increases (P<0.05) in medium chain FA, short chain and polyunsatured, n-3 concentration and reduced the n-6/n-3 ratio in the milk and the activity of the enzyme 9-desaturase (P=0.01), milk fat concentration (P=0.04) and tendency to reduce the total solids (P=0.08). Vitamin E increased the digestibility of the fibrous fraction (P<0.05), the milk reducing power (P=0.01), the 9-desaturase enzyme activity, the total antioxidant capacity in the blood (P=0.10) and reduced the production of TBARS (P=0.02). The interaction of the oil and the vitamin E promoted a tendency of increases in total antioxidant capacity (P=0.07) and milk reducing power (P=0.07). Both the addition of the oil and vitamin E reduced the rates of thrombogenicity and atherogenicity. Associating the lipid source with vitamin E is possible to obtain an improvement of the antioxidant activity in the buffalo's body, as well as to obtain an improved lipid profile and with good oxidative stability in buffalo milk.